Elucidating stygofaunal trophic web interactions via isotopic ecology - Saccò, Mattia; Blyth, Alison; Humphreys, W.F.; Kuhl, A.; Mazumder, D.; Smith, C.; Grice, Kliti (PUBLIC LIBRARY SCIENCE, 2019)
© 2019 Saccò et al.